Perfume Packaging, Seduction and Gender - Petersson McIntyre, Magdalena (Culture Unbound, 2013)
This article examines gender and cultural sense-making in relation to perfumes and their packaging. Gendered meanings of seduction, choice, consumption and taste are brought to the fore with the use of go-along interviews with consumers in perfume stores. Meeting luxury packages in this feminized environment made the interviewed women speak of bottles as objects to fall in love with and they de-scribed packages as the active part in an act of seduction where they were expecting packages to persuade them into consumption. The interviewed men on the other hand portrayed themselves as active choice-makers and stressed that they were always in control and not seduced by packaging. However, while their ways of explaining their relationship with packaging on the surface seems to confirm cultural generalizations in relation to gender and seduction, the article argues that letting oneself be seduced is no less active than seducing. Based on a combination of actor network theories and theories of gender performativity the article points to the agency of packaging for constructions of gender and understands the inter-viewees as equally animated by the flows of passion which guide their actions.